MENIN loss as a tissue-specific driver of tumorigenesis. (5th July 2018) - Li, Janet W.Y.; Hua, Xianxin; Reidy-Lagunes, Diane; Untch, Brian R.
Abstract: The MEN1 gene encodes MENIN, a tumor suppressor that plays a role in multiple cellular processes. Germline and somatic mutations in MEN1 have been identified in hereditary and sporadic tumors of neuroendocrine origins suggesting context-specific functions. In this review, we focus on the development of mutational Men1 in vivo models, the known cellular activities of MENIN and efforts to identify vulnerabilities in tumors with MENIN loss. Highlights: MEN1 encodes MENIN, a tumor suppressor that is altered in select cancers. Pancreatic neuroendocrine and parathyroid tumors are enriched with MEN1 mutations. Conventional and conditional mouse models of Men1 loss produce PanNETs. MENIN has GTPase activity and regulates transcription and the cell cycle.